Potential Analgesic of Ethanolic Extract Fruit and Seeds of Trembesi (Samanea saman (Jacq) Merr.) and Macroscopic Observations on the Gastric of Rats - Rosa Juwita Hesturini; Rachma Nurhayati; Nadia Pramasari (Sam Ratulangi University, 2023)
Trembesi (Samanea saman (Jacq.) Merr.) is a plant from the Fabaceae family known to the public as Ki Hujan. Trembesi fruit and seeds have several chemical compounds there are alkaloids, flavonoids, saponins, and tannins which have analgesic activity. This study aims to determine the dose of an extract of the fruit and seeds of trembesi which has analgesic activity but does not cause side effects in the form of irritation to the stomach of rats (Rattus norvegicus) macroscopically. A total of 40 rats were in 8 treatment groups, namely a negative control group of 0.5% CMC-Na, a positive control group of 500 mg acetosal, a group of 3, 4, 5 extracts of trembesi fruit at doses of 100, 200, 300 mg/kg BW, group 6, 7, 8 extracts of trembesi seeds at doses of 100, 200, 300 mg/kg BW. 0.7% acetic acid was induced in rats intraperitoneally as a pain inductor. The analgesic activity test was using the writhing test method and then the extract was continued for 7 days to determine the safety of the rat gastric. Data were analyzed using non-parametric Kruskal-Wallis and Man-Whitney. The results showed that the optimal ethanol extract of trembesi fruit and seeds was shown at a dose of 200 mg/kg BW with an analgesic power of 75,74% and 76,79% equivalent to acetosal which was 81.74% (Sig. > 0.05) with an ulcer index of 2 or otherwise not showed irritation of the stomach seen from the results of macroscopic observations of gastric. This study concludes that the ethanol extract of trembesi fruit and seeds at a dose of 200 mg/kg has the best analgesic activity and is safe for the stomach. Keywords: Analgetic; Samanea saman; trembesi; ulcer index